What drives students' Internet ethical behaviour: an integrated model of the theory of planned behaviour, personality, and Internet ethics education. Issue 3 (17th February 2022) - Wang, Yu-Yin; Wang, Yi-Shun; Wang, Yu-Min
ABSTRACT: With the emergence of Internet technology, Internet ethics has become an important issue for academics and practitioners. This study aims to investigate the factors that influence students' behavioural intention to perform an Internet ethical behaviour based on an integrated perspective of the theory of planned behaviour (TPB), Big-Five personality traits, and Internet ethics education. This study empirically examines the research model using a cross-sectional survey study, collecting data from a sample of 276 students, and using partial least squares (PLS) for the analysis. The results show that intention of performing Internet ethical behaviours is influenced by attitude toward ethical behaviour, subjective norms, and perceived behavioural control. Moreover, personality trait agreeableness is positively related to attitude toward ethical behaviour and subjective norms. Conscientiousness and openness are positively correlated with attitude toward ethical behaviour, subjective norms, and perceived behavioural control. Finally, the existence of an Internet ethics curriculum significantly strengthened the positive relationship between attitude toward ethical behaviour and intention of performing Internet ethical behaviours. The findings enhance our understanding of the relationship between students' Internet ethical behaviour and Internet ethics education. The results also provide several important theoretical and practical implications for Internet ethics education within the university education context.